2021
DOI: 10.3390/plants10020256
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Higher Levels of CO2 and Temperature and Their Interactions on Tomato (Solanumlycopersicum L.)

Abstract: Climate change has increasing effects on horticultural crops. To investigate the impact of CO2 and temperature at elevated levels on tomato production and quality of fruits an experiment was conducted by growing plants in open top chambers. The tomato plants were raised at EC550 (elevated CO2 at 550 ppm) and EC700 (elevated CO2 at 700 ppm) alone and in combination with elevated temperature (ET) + 2 °C in the open top chambers. These elevate CO2 and temperature treatment effects were compared with plants grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
4
10
1
Order By: Relevance
“…This improvement was compromised by a 2 °C temperature increase. Our results indicate that a further elevation of CO 2 up to 900 ppm generates similar results to Rangaswamy et al when considering sugar content [ 31 ]. If we did not assay the impact of temperature, we investigated protein and biological potential.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This improvement was compromised by a 2 °C temperature increase. Our results indicate that a further elevation of CO 2 up to 900 ppm generates similar results to Rangaswamy et al when considering sugar content [ 31 ]. If we did not assay the impact of temperature, we investigated protein and biological potential.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, total glucose was reported, by Rangaswamy et al [ 31 ] to be enhanced by 700 ppm CO 2 . This intermediary exposure, when compared to our study, was associated with better yield and qualitative fruit quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of CO 2 lessened the effects of high temperature and UV-B, resulting in lesser reductions. Interaction of high temperatures and elevated CO 2 increased plant height, the number of leaves, and leaf area in Fragaria x ananassa [ 86 ], Capsicum annuum [ 87 ], and Solanum lycopersicum [ 88 ]. In contrast to our results, Wang et al [ 71 ] reported reduced whole plant dry weight in rice under high temperatures and elevated CO 2 [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tomato fruit concentration of lycopene and β-carotene (pro-vitamin A) were found to increase in response to e [CO 2 ] by as much as 30% and 70% respectively [ 13 ]. Rangaswamy et al [ 25 ] reported an increase in carotenoid (+20%) and lycopene (+31%) in the fruits of tomato plants grown at 550 ppm [CO 2 ], however carotenoid content decreased (− 12%) when the concentration was increased to 700 ppm , suggesting that the level of CO 2 enrichment impacts fruit quality and careful consideration is needed to ensure an appropriate balance between levels of e [CO 2 ] and final yield. Lycopene is an important phytonutrient, is sold commercially as a dietary supplement, and has been reported to possess anti-cancer properties and can improve cardiovascular health [ 26 , 27 ].…”
Section: Impact Of Elevated [Co 2 ] On Yield and Q...mentioning
confidence: 99%